Health‐Seeking Behavior of Patients With Dental Abscesses: A Cross‐Sectional Study - Kwame Adu Okyere Boadu; Richard Okyere Boadu; Abigail Achiaa Nyarko; Esther Priscilla Biamah Danquah; Victor Wireko Adu; Nana Atuahene Oti; John Billy Owusu Quarshie; Nana Bempong Owusu‐ Ankomah (Health Science Reports)
ABSTRACT Background and Aims Dental abscesses are a common oral health issue that frequently remain untreated, resulting in severe health implications. This study evaluated the health‐seeking behaviour, knowledge, and attitudes of patients with dental abscesses at Komfo Anokye Teaching Hospital, Kumasi, Ghana. It further identified factors influencing patients' knowledge and practices, and examined the necessity of targeted educational interventions. Methods A cross‐sectional quantitative design was used to collect data from 100 participants through purposive sampling. Ethical approval was obtained from the Institutional Review Board of Komfo Anokye Teaching Hospital. Informed consent was obtained from all participants, who were provided with detailed information about the study's purpose, procedures, potential risks, and benefits. Written consent was obtained before participation. Descriptive statistics, χ2 tests, and bivariate logistic regression were employed to assess associations between socio‐demographic characteristics and knowledge of dental abscesses. Results The study found that 93% of patients had adequate knowledge of dental abscesses, recognizing severe tooth decay (4.43, SD = 0.73) and dental injuries (4.54, SD = 0.73) as primary causes. However, 54% of participants reported using home remedies, such as saltwater rinses, rather than seeking professional care. Bivariate logistic regression analysis revealed significant associations between age and anxiety, with patients aged 20–29 being more likely to experience anxiety (AOR = 9.76, 95% CI: [1.23–77.52], p = 0.031) compared to younger patients. Traders showed significantly higher likelihood of developing anxiety (AOR = 23.28, 95% CI: [2.71–200.06], p = 0.004) compared to unemployed individuals. Single patients were significantly less likely to experience anxiety (AOR = 0.10, 95% CI: [0.01–0.74], p = 0.024). Females (AOR = 0.39, 95% CI: [0.15–1.02], p = 0.055) and individuals with lower education levels showed marginally lower knowledge about dental abscesses. Conclusions The study highlights a need for targeted educational interventions to improve knowledge and encourage timely treatment of dental abscesses, particularly among females and individuals with lower educational levels. The findings can inform public health strategies aimed at reducing the burden of untreated dental abscesses in Ghana.